EVALUATION OF INFORMATION TECHNOLOGY GOVERNANCE MA-TURITY LEVEL FOR PROVISION WVI WAMENA BRANCH - Engelina Prisca Kalensun; Alina Wenda; Enius Wakerkwa; Desiriana Yikwa (STMIK Royal, 2023)
Abstract: Information Technology has been utilized by the Wahana Visi Indonesia Foundation in the process of managing goods data (Provision). Therefore, good and correct IT governance is needed by predetermined standards so that the use of IT for the foundation's operations can run well. The purpose of this study is to determine the extent to which management manages the processes of managing and evaluating IT performance, Internal Control, External Requirements, and IT Governance. Capability and maturity level measurements were carried out using the COBIT 2019 framework. The results obtained were that the capability level and maturity level values in the MEA 01 objective domain were 2.17 with a percentage of 41% categorized Partially, the MEA 02 objective domain obtained a value of 1 .97 with a percentage of 36% and entered the Partially category, the objective domain MEA 03 obtained a value of 2.11 with a percentage of 36% and entered the Partially category, the objective domain MEA 04 obtained a value of 1.75 with a percentage of 38% and entered the Partially category. Each process domain that is in it produces a gap level value or GAP value for each of the selected objective domains based on factor design. Domain MEA 01 got a score of 1.83, domain MEA 02 got a score of 2.03, domain MEA 03 got a score of 1.89, and domain MEA 04 got a score of 2.25 out of the expected maximum value of 4.00. Thus it can be concluded that the management and process evaluation of management is lacking and does not match existing targets or standards. Keywords: Capability; COBIT 2019; IT Governance; Maturity Abstrak: Teknologi Informasi sudah dimanfaatkan kegunaannya oleh Yayasan Wahana Visi Indonesia dalam proses pengelolaan data barang (Provision). Dengan demikian, dibutuhkan tata kelola TI yang baik dan benar sesuai dengan standar yang sudah diten-tukan agar penggunaan TI untuk operasional yayasan dapat berjalan dengan baik. Tujuan penelitian ini adalah untuk mengetahui sejauh mana manajemen mengelola proses-proses pengelolaan dan evaluasi kinerja TI, Internal Control, External Requirements dan Tata Kelola TI. Pengukuran capability dan maturity level dilakukan dengan menggunakan framework COBIT 2019. Hasil yang didapatkan berupa bahwa Nilai capability level dan maturity level pada domain obyektif MEA 01 adalah 2,17 dengan presntase 41% dikategorikan Partially, domain obyektif MEA 02 memperoleh nilai 1,97 dengan presentase 36% dan masuk kategori Partially, domain obyektif MEA 03 memperoleh nilai 2,11 dengan presentase 36% dan masuk kategori Partially, domain obyektif MEA 04 memperoleh nilai 1,75 dengan presentase 38% dan masuk kategori Partially. Setiap domain proses yang ada didalamnya menghasilkan nilai tingkat kesenjangan atau nilai GAP masing-masing dari setiap domain obyektif yang terpilih berdasarkan desain faktor. Domain MEA 01 mendapat nilai 1,83, domain MEA 02 mendapat nilai 2,03, domain MEA 03 mendapat nilai 1,89, domain MEA 04 mendapat nilai 2,25 dari nilai maksimal yang diharapkan 4,00. Dengan demikian bisa disimpulkan bahwa pengelolaan dan evaluasi proses dari manajemen sangatlah kurang dan tidak sesuai target atau standar yang ada. Kata kunci: Capability; COBIT 2019; Tata Kelola TI, Maturity